Chapter 9 Laser Pulses Characterization with Pyroelectric Sensors - Mazzoni, Marina; Capineri, Lorenzo (InTechOpen, 2010)
There are many industrial and medical applications of CO2 (λ=10.6 μm) and Nd:YAG (λ=1.06 μm) infrared lasers for which the quality of the process are tightly connected to the characteristic of the laser pulse. These two types of lasers deliver pulses with duration, repetition frequency and power that can be controlled by means of a programmable electronic control unit. An open-loop control generally optimize the process performances by availing of a laser system model. However, this method cannot control that during the operation the laser source and the optical delivering system could deteriorate; moreover the laser beam characteristics and laser pulse temporal envelope could change by several factors like power supply variations, optical beam misalignments, dirty deposits on mirrors, changes in laser efficiency and many others .